Evaluation of knowledge and education of physicians to diabetic patients in primary care in Saudi Arabia - Hassan, Khaled M.; Altooarki, Eman A.; Alshomali, Ahmad A.; Alhejeely, Othman A.; Almutairi, Mohammed A.; AlHarazi, Ghassan K.; Aljawi, Fahad W.; Alluqmani, Maha F.; Tashkandi, Abdulrahman M.; Almohussein, Nasser S.; Albishri, Abdulrahman T.; Kordi, Dania M.; et al. (International Journal Of Community Medicine And Public Health, 2020)
Background: Effective treatment of diabetes is not enough alone, there must be education and training from physicians and nurses to patients. To achieve education in correct manner there must be enough knowledge of physicians to apply care and teaching of these patients. The aim of the study was to evaluate the knowledge and education of physicians to diabetic patients in primary care in Saudi Arabia. Methods: Successive evaluation investigation through questionnaire. The work universe was made up of the 83 service areas of the 15 municipalities of Saudi Arabia, the sample of the total of the incorporated areas was initially made up of 625 health providers and 2,171 people with diabetes. Results: At the beginning of the study, the highest percentage of health providers surveyed declared that they did not know (78%) or that it was not defined (16.6) who should educate the person with diabetes, while the results at the end of the study show that 32% mentioned the doctor and the nurse and 62.7 the entire team of work (p=0.000) with a more adequate vision on the definition of responsibility for the fulfilment of this task and a generalized knowledge (97.5) of the existence of an education program in d diabetes that was useful for their compliance. Conclusions: Extension of the diabetes education program to Saudi Arabia achieved a significant change in the opinions of health providers on the health problem.